“I am afraid that others will feel scared and disgusted with me. So, I will keep it a secret until I die”: A qualitative study among patients with tuberculosis receiving DOTS regimen in Thailand - Koontalay, Apinya; Suksatan, Wanich; Prabsangob, Kantapong (Belitung Raya Foundation, Indonesia, 2021)
Background: Tuberculosis (TB) has become a significant public health problem leading to a top ten morality. Directly Observed Therapy, Short-course (DOTS) is recommended as a critical element for curing and preventing TB. However, patients who have been living with TB often receive barriers and challenges, which may lead them to discontinue the DOTS treatment. Objective: This study aimed to understand patients’ experiences living with TB and receiving DOTS regimens. Methods: A qualitative descriptive study was employed. Semi-structured interviews were done among twenty tuberculosis patients selected using convenience sampling from the slum community in Bangkok, Thailand. The thematic approach was used for data analysis. Results: Two main themes were developed: (1) troublesome disease and (2) emotional challenges. The first theme comprises three subthemes: confronting death, accepting lifestyle change, and DOTS challenges. The second theme consists of two subthemes: isolation from others and stigma. Conclusion: The findings could guide nurses and other healthcare professionals to develop the treatment guideline and the DOTS strategy using a holistic approach.